Selection of Sound Insulating Elements in Hydraulic Excavators Based Onidentification of Vibroacoustic Energy Propagation Paths - DĄBROWSKI, Zbigniew; DZIURDŹ, Jacek; PAKOWSKI, Radosław (Archives of Acoustics, 2013)
In spite of the fact that standardizing operations and increased awareness of hazards led to a significant improvement of vibroacoustic climate of operator’s stands of new machines, their long-term operation – often under difficult conditions – leads to a fast degradation of acoustic qualities of machines. Temporary operations performed during surveys and periodical overhauls are rarely effective, due to the lack of any guidelines. In this situation the authors propose the algorithm for selection of eventual screens or sound absorbing and sound insulating partitions, utilizing the measuring procedure aimed at identification, at the operator’s stand, of main noise components originated from various sources. On the basis of this procedure, the vibroacoustic energy propagation paths in the machine was estimated.